Analysis of burden of sexual assaults at Abuja: a 4-year retrospective study - Ayogu, Malachy Emeka; Abdullahi, Habiba Ibrahim; Adewole, Nathaniel D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Sexual assault is a worldwide crime associated with traumatic experience and largely affects women and girls. It is greatly underreported, more especially in the low income countries due to our peculiar culture. Methods: A retrospective study of sexual assault victims managed at the Hospital from January 1, 2015 to December 31, 2018. Case notes were retrieved and relevant data extracted and analyzed. Results: A total of 58 cases were seen and mostly involving pupils/students 44 (75.9%) and singles 52 (89.7%). The ages ranged from 3 to 37 years with a mean of 14.1±7.8. The assailants were known to the victims in 63.8% of cases. Sexual assault through vaginal route was the commonest type 57 (98.3%) and perpetrated by one person in majority of cases (79.0%). Physical force (43.1%) was major method used to subdue victims. About 60.3% of assaults occurred during the daytime and mainly occurred (60.4%) at home/office. The time interval between assault and presentation in the hospital ranged from 6 hours to 96 hours; majority presented within 24 hours (59.6%). Only 35 (60.3%) reported to the police. About 48.3% received post exposure prophylaxis. About 37.7% eligible for emergency contraception received it. Only 32.8% of the victims completed 3- month follow-up. Conclusions: Sexual assault is common in our environment with most victims being less than 14 years of age and assailants were mostly persons known to them. Some victims presented late.